VALIDITY OF ECOLOGY MISCONCEPTION TEST INSTRUMENT USING THREE-TIER TEST METHOD FOR 10TH-GRADE HIGH SCHOOL STUDENTS - Nugraha, Muhammad Izhar Mahendra Surya; Fitrihidajati, Herlina (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2021)
Biology is a science built on various concepts, one of them is the concept of ecology. The difference in conceptual understanding from what has been agreed by experts is described as a misconception that can impact decision making including students’ learning outcomes. It is crucial to identify the existing misconception in ecological material to avoid sustainable misconception during studying ecological material, because misconception can impact students’ learning outcomes during learning. This study aims to produce a valid ecology misconception test instrument for 10th-grade high school students. This research is development research conducted using 4D research design consisting of 4 stages, namely define, design, develop, and disseminate. This ecology misconception test instrument was developed using three-tier test method on ecology material to map students’ conceptual understanding of ecological material. The parameter used is the instrument test validity, including the content, construction, and language aspects determined by calculating the percentage of profit validity for each item according to the aspects tested. The validation process of this misconception test instrument was reviewed by 3 validators consisting of ecologists, assessment experts, and high school biology teachers. Validation is done by assessing each item on the suitability of the aspects being assessed, and the data was carried out in a descriptive quantitatively by calculating the percentage of instrument validity. Based on the results of the study, it is known that the ecology misconception instrument test with a three-tier test method developed was valid in the aspect of the material is 98,40%, construction is 94,58%, and language is 99,50% and the average result after analyzing for each question item is 98,95%. Keywords: misconception, ecology, instrument, validity.